Correlation of hand bone mineral density with the metacarpal cortical index and carpo:metacarpal ratio in patients with rheumatoid arthritis - Ozgocmen, S; Karaoglan, B; Kocakoc, E; Ardicoglu, O; Yorgancioglu, ZR (Yonsei Univ College Medicine, 1999)
This study proposed an assessment of the correlation of hand bone mineral density measured by dual energy x-ray absorbtiometry (DXA) with the carpo:metacarpal (C:MC) ratio and metacarpal cortical index (CI) in patients with rheumatoid arthritis (RA). The correlation of total hand BMD, CI and C:MC ratio with BMD at other sites, the Health Assessment Questionnaire (HAQ) and Larsen scores were also examined. The hand and axial BMD of 30 female patients were also compared with 29 age-matched healthy female controls. Total hand BMD values of patients were significantly lower than the control group. There was no significant difference between groups in axial measurements. CI correlated moderately with the second metacarp (II.MC) midshaft and total hand BMD. The C:MC ratio correlated with II.MC midshaft and total hand BMD. Total hand BMD correlated moderately with the AP spine (L2-L4) and femoral neck BMD. Larsen scores showed weak negative correlation with II.MC midshaft BMD and CI. Grip strength correlated weakly only with total hand BMD. The results indicated that CI may reflect cortical bone mass of the hand accurately and did not predict bone density of the spine or hip in patients with RA. The C:MC ratio is a useful method fur evaluating progression of wrist involvement and may be related to the loss of hand bone mineral density associated with disease process.
Keywords: hand bone mineral density; rheumatoid arthritis; cortical index; carpo : metacarpal ratio